THE ADVANTAGES OF NON-INVASIVE BRAIN STIMULATION FOR PATIENTS WITH MAJOR DEPRESSIVE DISORDER (MDD) - Reza Amelia Ahidatun Nabila (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2022)
Background : Depression, reduced interest, cognitive impairment, and symptoms of vegetative growth such as sleep problem and low appetite are all signs of major depressive disorder (MDD). Depression is the fifth biggest cause of disability in Indonesia, with a prevalence of 6.1 percent. The treatment choices for major depressive disorder are psychotherapy and medication, both of which are successful in treating major depressive disorder. Despite this, doctors are confronted with clinical circumstances that are resistant to therapy or do not respond to it. For refractory individuals who have not responded to a variety of augmentation procedures or a combination of therapies, brain stimulation that is not invasive such as repeated transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) is an option.Method : Researchers employed the literature review approach to compile the results of numerous publications that cover major depression and brain stimulation that is not invasiveÂ in depressed patients for this study.Conclusion : The illness effects and limits of current pharmacological and psychological methods highlight the necessity for non-invasive brain stimulation as an alternate therapy approach. Repeated TMS may aid with depressive symptoms and cognitive tasks linked to the etiology of depression. Regardless of whether rTMS and antidepressants have similar effects, combining the two is more effective than using rTMS alone. tDCS, in combination to rTMS, might be used to treat severe depressive disorder. In individuals who are hesitant to take drugs or who are unable to handle antidepressants, tDCS may be a viable option. In non-drug resistant major depression, tDCS is likely to be successful, while in drug-resistant major depression, it is likely to be unsuccessful.